PEMANFAATAN ILES-ILES (AMORPHOPHALLUS ONCOPHYLUS)SEBAGAI BAHAN PENGENYAL PADA PEMBUATAN TAHU - Citra Perdani Utami; Sukma Ayu Fitrianingrum; Kristinah Haryani (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2012)
Ussually, boraks is used in the process of making tofu, thouhg it has many disadvantages for the body. That’s why, an alternative must be found to replace boraks. Iles-iles which has high content of glukomanan is used to replace boraks.The purpose of this study was to determine the effect of adding iles-iles of elasticity know, on nutrition knows, and knows the storage time with the addition of iles-iles. In this study, the material needed is soybeans, iles-iles, distilled water and CaO. That has been boiled soy blend to a temperature of 900C. After that, soy milk is filtered and mixed with tubers iles-iles that have been boiled and dilaluskan. CaO was added to adjust pH. Know who has been so analyzed for levels of protein, crude fiber, as well as the resilience and durability.From the analysis of proteins, can be compared to know the normal levels of protein levels of the protein out with the addition of iles-iles higher protein damage due to borax in regular knows. For the analysis of fiber, protein levels of crude fiber in the plus-iles iles higher because of the iles-iles contain lots of fiber. Elasticity know the iles-iles lower than usual idea, because borax is more rubbery. Know that contain glucomannan seawet not know which contain borax.Conclusions obtained from this study, out with the addition of iles-iles had higher levels of nutrients that knows more than the usual. However, elasticity and durability of iles-iles out with less than know with borax, because iles-iles has a lot of water content